Predictive Role of Platelet-Associated Indices on Admission and Discharge in the Long-Term Prognosis of Acute Coronary Syndrome Patients. (May 2022) - Psarakis, Georgios; Farmakis, Ioannis; Zafeiropoulos, Stefanos; Kourti, Olga; Konstantas, Orestis; Vrana, Eleni; Baroutidou, Amalia; Tsolakidis, Christos; Touriki, Aikaterini-Vassiliki; Psathas, Thomas; Graidis, Spyridon; Spyridaki, Konstantina; et al.
Our study aimed to investigate the association between platelet indices and their in-hospital change and long-term prognosis in acute coronary syndrome (ACS). Data from a randomized controlled trial (NCT02927808) recruiting ACS patients were analyzed (survival analysis). The examined variables were platelet count (PC), mean platelet volume (MPV), platelet distribution width (PDW), and plateletcrit (PCT) on admission and discharge, as well as their alteration during hospitalization. The primary endpoint was major adverse cardiac events (MACE) (cardiovascular death, non-fatal myocardial infarction, and non-fatal stroke or hospitalization for unstable angina) and all-cause mortality, while secondary endpoints were all-cause hospitalization and bleeding events. The study included 252 patients with a follow-up of 39 (28–45) months. In the univariate analysis, MACE was associated with discharge PC [hazard ratio (HR) 2.20, 95% confidence interval (CI) 1.10–4.40], discharge MPV (HR 0.48, 95% CI 0.25–0.94), and in-hospital PC difference (HR 0.25, 95% CI 0.13–0.51). In the multivariable analysis, only in-hospital PC decrease correlated with lower MACE incidence (adjusted HR .27, 95% CI 0.14–0.54) and lower all-cause hospitalization risk (adjusted HR 0.36, 95% CI 0.19–0.68). PC reduction during hospitalization for ACS is an independent predictor of better prognosis.